Water Reuse - An International Survey of Current Practice, Issues and Needs - Asano Takashi; Jiménez Blanca (Scientific and technical report, 2008)
This book examines water reuse practices around the world from different perspectives. The objective is to show how differently wastewater reuse is conceived and practised around the world as well as to present the varied needs and possibilities for reusing wastewater. This book will be an invaluable information source for all those concerned with water reuse including water utility managers, wastewater policy makers and water resources planners as well as researchers and students in environmental engineering, water resources planning and sanitary engineering.